"I Had One Job and That Was To Make Milk": Mothers' Experiences Expressing Milk for Their Very-Low-Birth-Weight Infants. (February 2017) - Bower, Katherine; Burnette, Tara; Lewis, Daniel; Wright, Courtney; Kavanagh, Katie
Background: For very-low-birth-weight (VLBW) infants, breastfeeding may no longer be an immediate option. Mothers often turn to mechanically expressing their milk with a breast pump to provide their infants human milk. Research aim: This study aimed to describe mothers' experiences expressing milk for their VLBW infants in a level 3 neonatal intensive care unit. Methods: Qualitative, phenomenological methods were used to better understand the milk expression experiences of 17 mothers of VLBW infants. In-depth interviews were audio-recorded and transcribed verbatim. Transcripts were analyzed using Colaizzi's seven-step protocol, and themes were identified to illustrate the lived experience of the mothers. Results: Five global themes emerged from interviews with mothers. However, this article focuses on one global theme, "I had one job and that was to make milk, " and the supporting subthemes: (1) "I was heartbroken, " (2) "Pumping is a full-time thing, " and (3) "I literally sacrificed nights." Conclusion: This study provides insight into the complex experience that mothers in the southeastern United States undergo when expressing milk for their VLBW infants.